HANDLING OF PROBLEMATIC FINANCING ON THE MURᾹBAḤAH CONTRACT AT PT. BANK SYARIAH MANDIRI SIBOLGA BRANCH OFFICE - NOFINAWATI nofinawati; muhammad wandisyah; kharisma kharisma (Institut Agama Islam Negeri Padangsidimpuan, 2022)
This research is motivated by the large number of customers who have had problems with murābaḥah contracts from 2015 to 2018. In 2015 there were 329 people, in 2016 it decreased to 251 people. But in 2017 the number of problem financing customers increased to 295 people and in 2018 there were 343 people. The formulation of the problem in this study is twofold, firstly what are the factors that cause financing problems in the murābaḥah contract at PT? Bank Syariah Mandiri Sibolga Branch office with the aim of research to find out the factors that cause financing problems in the murābaḥah contract at PT. Bank Syariah Mandiri Sibolga Branch Office. Secondly, how to deal with problematic financing in the murābaḥah contract at PT. Bank Syariah Mandiri Sibolga Branch office with the aim of research to determine the handling of problem financing in the murābaḥah contract at PT. Bank Syariah Mandiri Sibolga Branch Office. This research is qualitative research, the data source used is primary data and secondary data. Data collection techniques used were interviews and documentation. The results showed that the factors causing problematic financing at Bank Syariah Mandiri Sibolga Branch Office were caused by two factors namely, internal factors which consisted of weak analysis, lack of supervision of the flow of funds, and disorderly administration. And external factors consist of customer lifestyle, bad faith, declining business conditions, and business competition. Handling problematic financing is done by billing via telephone and direct billing to the place of the customer. Then the other way is by restructuring which consists of three stages, namely rescheduling, reconditioning, and restructuring and the last way is by carrying out a guarantee execution.